Heart rate monitoring during training and competition in cyclists - Jeukendrup, A.; Diemen, A. van (Journal of Sports Sciences, 1998)
To obtain optimal training effects and avoid overtraining, it is necessary to monitor the intensity of training. In cycling, speed is not an accurate indicator of exercise intensity, and therefore alternatives have to be found to monitor exercise intensity during training and competition. Power output may be the most direct indicator, but heart rate is easier to monitor and measure. There are, however, limitations that have to be taken into account when using a heart rate monitor. For example, the position on the bicycle may change heart rate at a given exercise intensity. More important, however, is the increase in heart rate over time, a phenomenon described as `cardiac drift`. Cardiac drift can change the heart rate-power output relationship drastically, especially in hot environments or at altitude. It is important to determine whether one is interested in monitoring exercise intensity per se or measuring whole-body stress. Power output may be a better indicator of the former and heart rate may, under many conditions, be a better indicator of the latter. Heart rate can be used to evaluate a cyclist after training or competition, or to determine the exercise intensity during training. Heart rate monitoring is very useful in the detection of early overtraining, especially in combination with lactate curves and questionnaires. During overtraining, maximal heart rates as well as submaximal heart rates may be decreased, while restingand, in particular, sleeping - heart rates may be increased.